2006
DOI: 10.1016/j.jvs.2005.11.054
|View full text |Cite
|
Sign up to set email alerts
|

Vocal cord paralysis after aortic arch surgery: Predictors and clinical outcome

Abstract: The risk of vocal cord paralysis after aortic arch surgery depends on surgical factors, such as aneurysmal involvement of the distal arch, or the application of newer, less invasive surgical procedures. Vocal cord paralysis after aortic arch surgery itself, under aggressive postoperative respiratory management, did not increase aspiration pneumonia but was associated with postoperative complications leading to higher hospital mortality and prolonged hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 23 publications
3
52
0
1
Order By: Relevance
“…Recurrent nerve injury after arch surgery is reported to be an independent predictor of postoperative pulmonary complications and leads to a longer hospital stay. 15 Postoperative vocal cord paralysis was not observed in our patients, mainly because the dissection, incision, and sutures of the distal arch and the descending aorta were not necessary and thus recurrent nerve injury was avoided.…”
Section: Discussionmentioning
confidence: 75%
“…Recurrent nerve injury after arch surgery is reported to be an independent predictor of postoperative pulmonary complications and leads to a longer hospital stay. 15 Postoperative vocal cord paralysis was not observed in our patients, mainly because the dissection, incision, and sutures of the distal arch and the descending aorta were not necessary and thus recurrent nerve injury was avoided.…”
Section: Discussionmentioning
confidence: 75%
“…Ishii and colleagues [7] reported that 9% of 156 patients had the complication after thoracic aortic aneurysm repair. Ohta and colleagues [1] documented a 22% incidence of VCP in 183 patients undergoing aortic arch aneurysm repair and described the consequent pulmonary complications. DiLisio and colleagues [8] described a series of 498 patients who underwent thoracic aortic aneurysm repair, and noted an incidence of VCP of 7.2% in the arch and descending aortic repair group.…”
Section: Commentmentioning
confidence: 99%
“…In addition, glottic incompetence secondary to VCP in the postoperative patient may result in an ineffective cough, tracheal aspiration, and an increased risk of subsequent pneumonia and respiratory failure. Previous authors [1,8] have presented results suggesting that VCP may lead to an increased incidence of tracheostomy and result in a longer postoperative hospital length of stay. The results of our propensitymatched analysis also suggest that VCP is associated with an increased risk of pneumonia and a longer hospital length of stay.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Totally 50 reported were collected, including 19 (38%) case reports or case series [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], 1 (2%) technique [30], 17 (34%) retrospective [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] and 13 (26%) prospective reports [7,11,[49][50][51][52][53][54][55][56][57][58][59].…”
Section: Resultsmentioning
confidence: 99%